Agar Disk Diffusion and Automated Microbroth Dilution Produce Similar Antimicrobial Susceptibility Testing Results for Salmonella Serotypes Newport, Typhimurium, and 4,5,12:i-, But Differ in Economic Cost - Hoelzer, Karin (Mary Ann Liebert, Inc., 2011)
Data generated using different antimicrobial testing methods often have to be combined, but the equivalence of such results is difficult to assess. Here we compared two commonly used antimicrobial susceptibility testing methods, automated microbroth dilution and agar disk diffusion, for 8 common drugs, using 222 Salmonella isolates of serotypes Newport, Typhimurium, and 4,5,12:i-, which had been isolated from clinical salmonellosis cases among cattle and humans. Isolate classification corresponded well between tests, with 95% overall category agreement. Test results were significantly negatively correlated, and Spearman's correlation coefficients ranged from −0.98 to −0.38. Using Cox's proportional hazards model we determined that for most drugs, a 1 mm increase in zone diameter resulted in an estimated 20%–40% increase in the hazard of growth inhibition. However, additional parameters such as isolation year or serotype often impacted the hazard of growth inhibition as well. Comparison of economical feasibility showed that agar disk diffusion is clearly more cost-effective if the average sample throughput is small but that both methods are comparable at high sample throughput. In conclusion, for the Salmonella serotypes and antimicrobial drugs analyzed here, antimicrobial susceptibility data generated based on either test are qualitatively very comparable, and the current published break points for both methods are in excellent agreement. Economic feasibility clearly depends on the specific laboratory settings, and disk diffusion might be an attractive alternative for certain applications such as surveillance studies.